All-cause and Cause-Specific Excess Deaths during the COVID-19 Pandemic - Margherita Pizzato; Claudia Santucci; Carlo La Vecchia; Gianfranco Alicandro (Epidemiology, Biostatistics and Public Health)
We estimated the excess mortality during the COVID-19 pandemic (2020-2023) in selected countries worldwide. In Europe, half a million excess deaths occurred annually in the first three years of the pandemic, while a 2.1% excess was observed in 2023 (108,629 deaths). Significant excess mortality was recorded worldwide for all-cause mortality, cardiovascular disease, and diabetes, with peaks in COVID-19 cases closely aligning with these excess deaths. No increase in cancer-related mortality was observed. Gross domestic product per capita, national health expenditure, and vaccination rates were inversely associated with excess mortality. These findings provide insights into the public health impact of COVID-19 and inform future policy decisions.